2015
DOI: 10.1128/aac.00512-15
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopalladated Compound 7a Induces Apoptosis- and Autophagy-Like Mechanisms in Paracoccidioides and Is a Candidate for Paracoccidioidomycosis Treatment

Abstract: c Paracoccidioidomycosis (PCM), caused by Paracoccidioides species, is the main cause of death due to systemic mycoses in Brazil and other Latin American countries. Therapeutic options for PCM and other systemic mycoses are limited and time-consuming, and there are high rates of noncompliance, relapses, toxic side effects, and sequelae. Previous work has shown that the cyclopalladated 7a compound is effective in treating several kinds of cancer and parasitic Chagas disease without significant toxicity in anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…The defects of autophagy are associated with neurodegeneration, aging, metabolic syndrome, and inflammatory disorders. 25 The TEM results presented in this study revealed that the accumulation of autophagosomes was increased in corneas of patients with FK compared with healthy donors. Next, we established A. fumigatus keratitis models to further determine the expression of autophagy.…”
Section: Discussionmentioning
confidence: 48%
“…The defects of autophagy are associated with neurodegeneration, aging, metabolic syndrome, and inflammatory disorders. 25 The TEM results presented in this study revealed that the accumulation of autophagosomes was increased in corneas of patients with FK compared with healthy donors. Next, we established A. fumigatus keratitis models to further determine the expression of autophagy.…”
Section: Discussionmentioning
confidence: 48%
“…A role for the P. anserina cyclophilin D ortholog in RCD 343 344 345 as well as for autophagy in aging and lifespan control of P. anserina 346 347 have been reported. Further instances of fungal RCD 306 348 have been documented in Paracoccidioides brasiliensis 349 , Colletotrichum gloeosporioides 350 , Fusarium oxysporum 351 , Fusarium graminearum 352 , Mucor racemosus 353 , Botrytis cinerea 354 , Penicillium expansum 355 , Rhizopus oryzae 356 , Scedosporium prolificans 357 and Neurospora crassa 358 . As multicellular organisms, filamentous fungi have developed programs that are reminiscent of organismal RCD.…”
Section: Rcd In Other Yeasts and Filamentous Fungimentioning
confidence: 99%
“…In P . brasiliensis , apoptosis and autophagy-like mechanisms have recently been implicated in a cyclopalladated 7a-mediated cell death [ 32 ]. Gontijo et al [ 33 ] showed that 21 of 34 autophagy-related genes described in Saccharomyces cerevisiae are present in a basidiomycete, Cryptococcus neoformans , and in Candida albicans and Aspergillus fumigatus , both ascomycetes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies about the mechanisms responsible for triggering autophagy in Paracoccidioides spp , as well as the occurrence of the autophagic process itself, have only been initiated very recently with a single demonstration made by Arruda et al [ 32 ] that mechanisms resembling autophagy-like cell death may be behind the cyclopalladated 7a compound killing of P . brasiliensis .…”
Section: Introductionmentioning
confidence: 99%